The Importance of the Sustainability of Environmental Accounting - Akdoğan, Habib; Hicyorulmaz, Ela (Journal of Economic Development, Environment and People, 2015)
: Rapid population growth, industrialization, unplanned urbanization, global warming, tourism activities and natural disasters have resulted in environmental issues that have reached global dimensions and started to threaten the life of creatures. For the permanent protection of ecological balance and sustainability, massive national and international regulations are needed. Threatening the life of creatures has not been considered in the system consisting of the establishment of equilibrium between man and nature as required. At this point businesses have important responsibilities. Businesses, for example, in order to prevent environmental pollution waste control systems, filtration systems, recycling methods etc. endured environmental costs in a variety of ways, as these costs are incurred also causes more businesses to see the value of protecting the environment. The result of the activities of environmental impacts of enterprises can be considered, to be taken in the preparation of the necessary data to guide decisions, contacts and presentation of the stages of the environmental accounting system. In this study, we first examine the concepts of environmental accounting, sustainability and environmental costs and then in the cement factories located in Turkey the environmental costs and environmental accounting will be given in the results of a survey made for the calculation of the sensitivity. Keywords: Environmental Accounting; Sustainability; Environmental Costs